In Vitro Assessment of Mutagenic And Genotoxic Effects of Coumarin Derivatives 6,7-Dihydroxycoumarin and 4-Methylesculetin - Maistro, Edson Luis [UNESP]; Marques, Eduardo de Souza [UNESP]; Fedato, Rafael Palhano [UNESP]; Tolentino, Flora [UNESP]; Cezario da Silva, Chayene de Andrade [UNESP]; Ferreira Tsuboy, Marcela Stefanini [UNESP]; Resende, Flavia Aparecida [UNESP]; Varanda, Eliana Aparecida [UNESP] (Taylor & Francis Inc, 2015)
Coumarins are naturally occurring compounds, widely distributed throughout the plant kingdom (Plantae), and possess important pharmacological properties, including inhibition of oxidative stress. In this context, newly synthesized coumarin compounds are being produced due to their potent antioxidant activities. Therefore, the aim of the present study was to determine the in vitro cytotoxic, mutagenic, and genotoxic effects of 6,7-dihydroxycoumarin (6,7-HC) and 4-methylesculetin (4-ME) using the Salmonella/microsome test and in cultured human lymphocytes the comet assay and micronucleus test. The three coumarin derivatives concentrations evaluated in comet and MN assays were 2, 8, and 32 mu g/mL, selected through a preliminary trypan blue-staining assay. In the Ames test, the 5 concentrations tested were 62.5, 125, 250, 500, and 750 mu g/plate. Positive (methyl methane-sulfonate, MMS) and negative (dimethyl sulfoxide, DMSO) control groups were also included in the analysis. Our results showed that 4-ME induced greater cytotoxicity at high concentrations than 6,7-HC. In addition, both compounds were not mutagenic in the Ames test and not genotoxic or clastogenic/aneugenic in cultured human lymphocytes.